Astragaloside IV Inhibits Galactose-Deficient IgA1 Secretion via miR-98-5p in Pediatric IgA Nephropathy - Liu, Caiqiong; Li, Xiaoyan; Shuai, Lanjun; Dang, Xiqiang; Peng, Fangrong; Zhao, Mingyi; Xiong, Shiqiu; Liu, Ying; He, Qingnan (Frontiers in Pharmacology, 2021)
Purpose: The factor associated with IgA nephropathy (IgAN) is an abnormality of IgA known as galactose-deficient IgA1 (Gd-IgA1). The purpose of this study was to determine the molecular role played by miRNAs in the formation of Gd-IgA1 in IgAN and investigate the regulatory role of Astragaloside IV (AS-IV) in miRNAs. Patients and methods: Bioinformatics analysis, along with functional and mechanistic experiments, were used to investigate the relationship and function of miRNA, β-1, 3-galactosyltransferase (C1GALT1), Gd-IgA1, and AS-IV. Analyses involved a series of tools, including quantitative real-time polymerase chain reaction (qRT-qPCR), Western blot, enzyme-linked immunosorbent assay ( ELISA), Vicia Villosa lectin-binding assay ( VVA), Cell counting kit-8 assay (CCK-8), and the dual-luciferase reporter assay. Results: miRNA screening and validation showed that miR-98-5p was significantly upregulated in the peripheral blood mononuclear cells ( PBMCs) of pediatric patients with IgAN compared with patients diagnosed with mesangial proliferative glomerulonephritis (MsPGN) and immunoglobulin A vasculitis nephritis (IgAV-N), and healthy controls (p<0.05). Experiments with the dual-luciferase reporter confirmed that miR-98-5p might target C1GALT1. The overexpression of miR-98-5p in DAKIKI cells decreased both the mRNA and protein levels of C1GALT1 and increased the levels of Gd-IgA1 levels; these effects were reversed by co-transfection with the C1GALT1 plasmid, and vice versa. In addition, AS-IV downregulated the levels of Gd-IgA1 level in DAKIKI cells by inhibiting miR-98-5p. Conclusion: Our results revealed that AS-IV could inhibit Gd-IgA1 secretion via miR-98-5p. Increased levels of miR-98-5p in pediatric IgAN patients might affect the glycosylation of IgA1 by targeting C1GALT1. In addition, our analyses suggest that the pathogenesis of IgAN may differ from that of IgAV-N. Collectively, these results provide significant insight into the pathogenesis of IgAN and identify a potential therapeutic target.